Comparison of Indonesian and Malaysian Character Education - Marzam Marzam; Depi Elpina; Rusdinal Rusdinal; Azwar Ananda; Nurhizrah Gistituati (Goodwood Publishing, 2022)
Purpose: This study aims to determine the comparison of policies between Indonesia and Malaysia. His comparison is needed to develop Indonesian education policies so that the quality of Indonesian education policies in the future will be better. Methodology: The research method uses literature study due to it compares education policies. Especially character education between Indonesia and Malaysia. Results: The results showed that Indonesia’s’ education policies were still categorized as low because it was based on the four components being compared, namely character education goals, character education strategies, education structures, and education management. Conclusions: Indonesia’s education policy is based on Pancasila and the 1945 Constitution, while Malaysia’s retains colonial influences. Malaysia appears more advanced due to free education and broader community support across key policy components. Limitations: This study focuses on four components of education policy, particularly character education. There are other parts that can be discussed by further research, namely other parts of Education policy and can also be compared with other countries. Contributions: This research can be a consideration for Indonesian policy holders, especially the aspect of character education because it can improve the quality of Indonesian education.